Impact of ambient temperature on the cooling of power transformers: a CFD investigation for regions of the state of Espírito Santo - Feroni, Rita de Cassia; Viana, Joyce Tamires de Souza; Maionchi, Daniela de Oliveira; Monteiro, Raul Vitor Arantes; Fonseca, André Luiz Amorim da; Feroni, Wilson José; Silva, Junior Gonçalves da (Brazilian Journal of Production Engineering, 2026)
Electrical transformers are being studied to increase energy efficiency and reduce environmental impact. In this context, the objective of the present work is to evaluate, using computational fluid dynamics (CFD), the impact of ambient temperature on the cooling of electrical transformers for different temperature values, covering the climatic conditions of regions in the state of Espírito Santo, Brazil. A 250 kVA electrical transformer was studied using CFD, with the air temperatures of the municipalities of interest applied as boundary conditions in the modeling. The results show that february is historically the hottest month, with the highest average maximum temperature in Alegre at 34.2 °C, and peak temperatures were recorded in Marilândia (42.1 °C) and Ecoporanga (40.0 °C). From the computational simulation, it was observed that temperature is distributed from its maximum values near the surfaces of the coils and the core to its minimum values at the external surfaces of the transformer. The average and maximum oil temperatures increase as the ambient temperature rises, due to the decrease in heat dissipation to the outside. This result suggests that greater attention should be given to devices installed in the municipalities of Alegre, Marilândia, and Ecoporanga.